Penerapan Network Monitoring di Dinas Komunikasi dan Informatika Kabupaten Asahan - Herman Saputra; Sahren Sahren; Elly Rahayu; Aidil Syah Putra (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
The implementation of network monitoring at the Asahan Regency Information and Communication Service using LibreNMS aims to increase network management efficiency and minimize downtime.  LibreNMS, as an open-source network monitoring platform, enables early detection of problems in network devices such as routers, switches, and servers.  During this deployment, various metrics such as bandwidth usage, device health, and network performance are monitored in Real-Time.  This system also supports automatic telegram notifications if a disruption occurs, thereby speeding up the processing process. With this comprehensive monitoring, agencies can optimize network infrastructure, reduce the risk of service disruptions, and improve the quality of public services. The results of this deployment show increased network stability and operational efficiency at the Asahan Regency Information and Communication Service.